D4N2024 Presentation Showcase – Thematic Session 2a: Methods and metrics to improve nutrition through sustainable agriculture - Hasan, Mohammad Monirul; Islam, Saiful; Gathala, Mahesh Kumar; Hossain, Md. Khaled; Rahman, Md. Arifur; Mithu, Mehedi Hassan; Hoque, Muhammad Arshadul; Pandit, Dinabadnhu; Mia, Shamim; Krupnik, Timothy J.; Faisal, Mohammad Washiq; Sapkota, Sujan; et al. (International Food Policy Research Institute, 2024)
Oral Presentations: Reducing Carbon Footprint in Agriculture through Conservation and Efficient Nutrient Management Practices: A Case Study of Bangladesh Md Saiful Islam, Research Coordinator, International Maize and Wheat Improvement Center (CIMMYT)